The importance of winning football games at youth level: Player and coach perspectives - Ian David Jeffs 1982- (2011)
The purpose of this study was to determine if youth coaches in Iceland were over-emphasising the desire to win games in youth football. The research was conducted to see if winning games was prioritized by coaches ahead of developing football ability and football understanding of their players. The research also looked into the issues of burnout and overuse, to see if young players were at increased risk of the fore mentioned. I used both a quantitative and qualitative approach towards my research methods when collecting the data. 204 participants from four different clubs in the Reykjavik area aged between the ages 13-19 took part in answering a questionnaire. Interviews with the four head coaches of the same clubs were then conducted. Results indicated that why winning may be heavily emphasized by youth coaches it doesn„t obstruct the development of the players and their progress towards improving as football players. Evidence from this research showed that winning games may be more associated to parental pressure on the coaches, which in turn increases the expectation levels. Further research should be focused on this particular aspect of youth football in Iceland to assess the needs of the coach/parent relationships in youth football.